Phytochemical study of flavonoids from the leaves of muntingia calabura, synthesis of flavonoid mannich base derivatives and their anticancer activity against breast carcinoma cell lines - Chang, Chew Cheen (2023)
Due to the continuous evolution of multi-drug resistant tumors, the development of new drugs with enhanced efficacy is essential. Hence, there is a growing interest in making chemical modifications to the natural flavonoids to improve the bioactivity. The aim of this study is to extract, isolate and characterize the chemical constituents from the leaves of Muntingia calabura, synthesize and characterize flavonoid Mannich base derivatives and evaluate their cytotoxic activity. Initially, dried leaves of Muntingia calabura were extracted with 95% ethanol, followed by 1:1 water/ethyl acetate (EA) partition. The EA crude extract was then subjected to continuous column chromatography over silica gel to obtain pure compounds. The pure compounds were characterized by spectroscopic techniques. Subsequently, the isolated flavonoids were subjected to Mannich reaction. The synthesized compounds were characterized by spectroscopic techniques. Cytototoxic activity of the parent compounds and synthesized compounds were evaluated against two breast cancer cell lines i.e., MCF-7, MDA-MB-231, and one normal breast cell line, MCF-10A via MTT assay. A total of eighteen flavonoids were isolated from the leaves of Muntingia iii calabura. Among them, 3,5-dihydroxy-7-methoxyflavanone (M1), 7,8- dihydroxyflavanone (M17), and 2’,3’,4’-trihydroxychalcone (M6) were isolated from the leaves of Muntingia calabura for the first time. For Mannich bases, a total of twenty flavonoid Mannich bases were synthesized. Cytotoxic activity against MDA-MB-231 cancer cell line showed that flavonoid Mannich bases exhibited greater activity than parent compounds. 5,7-dihydroxy-8-(4- methoxybenzylamine)-2-phenyl-4H-chromen-4-one (M14f) showed the highest cytotoxic activity against MDA-MB-231 cell with IC50 of 5.75±0.82 µM. For MCF-7 cell line, the parent compounds and Mannich bases showed moderate activity with the IC50 range of 9.17-68.5 µM. For cytotoxic activity against MCF-10A cell line, parent compounds, 5,7-dihydroxyflavone (M14) showed highest toxicity against MCF-10A with IC50 of 10.55±1.05 µM. The results suggest that synthetic modifications have produced the compounds with improved anticancer activity and selectivity against breast cancer cells.